Sand body architecture of braided river deltas in the Upper Triassic Xujiahe Formation, Sichuan Basin - Yanqing Huang; Meizhou Deng; Nan Duan; Wujun Jin; Junlong Liu; Na Niu; Ai Wang; Xiaolin Lu (Energy Geoscience)
The recent discovery of natural gas within the fifth member of the Xujiahe Formation (T3x5) in the Dongfeng area within the Sichuan Basin highlights the significant exploration potential of this member. However, the unconvincing previous understanding of the sedimentary microfacies, combined with a total lack of studies on the sand body architecture and reservoir distribution, hampers the further exploration of this member. Using core data, log curves, and seismic data, along with sedimentary microfacies analysis, this study investigated the interfaces between the sand bodies of various scales in the Dongfeng area. Furthermore, this study explored the morphological characteristics, types, and stacking patterns of these sand bodies and determined the distributions of sand bodies and reservoirs in the area. The results indicate that the first sand group of the T3x5 member (T3x51) exhibits delta-front deposits, including subaqueous distributary channels, sheet sands, and interdistributary bays. Seven levels of sand body interfaces are identified in the T3x51 sand group. Among them, the interfaces of the first and second levels were identified only in cores, those of the third and fourth levels were recognizable from cores combined with log curves, while those of the fifth, sixth, and seventh levels were distinguishable using seismic data. Three superimposed subaqueous distributary channel complexes are found in the Dongfeng area. Among them, complex 1 in the northwest exhibits the strongest water body energy, while complex 2 in the south displays the weakest. Complex 2 was formed earlier than complexes 1 and 3. Also, complex 1 is further subdivided into three vertically stacked subaqueous distributary channels. The subdivision of sedimentary microfacies in the T3x5 member reveals nine lithofacies types. Among them, stacked pancake-shaped, carbonaceous debris-bearing, massive, and cross-bedded medium-grained sandstones are considered favorable lithofacies. These four lithofacies types exhibit high porosity, as well as low natural gamma-ray (GR) values, low-to-medium deep investigate double lateral resistivity (RD), and high interval transit time (AC) on the log curves. Additionally, the reservoir distribution in the Dongfeng area was delineated based on the characterization of the favorable lithofacies. This study serves as a guide for future exploration and evaluation of the T3x5 member in the Dongfeng area while also augmenting the methodologies for describing tight sandstone reservoirs.